Prediksi Jejak Karbon Fakultas Sains dan Teknologi Kampus Pinang Masak Universitas Jambi - Nurhayat Nurhayat; Rizki Andre Handika (Universitas Batanghari Jambi, 2019)
The existence of Universities that include many human activities for energy consumption such as electrical and fossil fuel energy would be affected to CO2 emission. As the most important component of greenhouse gases (GHG), CO2 will induce global warming, which become climate change condition. This research was intended to predict the amount of CO2 emission from campus activities using International Panel Climate Change (IPCC) method. Location for the research sample was in Faculty of Science and Technology (FST), Pinang Masak Campus of Jambi University, which the carbon emission sources were identified to three scope based on The Greenhouse Gas Protocol. Carbon footprint scope 1 comprises from operational vehicle activities and use of LPG in Canteen in aggregate 12,18 ton.CO2-eq. However, scope 2 comes from the use of electrical which amount to 100,29 ton.CO2-eq and scope 3 which consist of transportation activities and the use of paper by FST lecturers, staff and students with amount 443,64 ton.CO2-eq. Therefore, the total amount of carbon footprint in FST Campus was 556,10 ton.CO2-eq.